Highly selective adsorption of perfluorinated greenhouse gases by porous organic cages [data] - Tian, Ke; Elbert, Sven; Hu, Xin-Yue; Kirschbaum, Tobias; Zhang, Wen-Shan; Rominger, Frank; Schröder, Rasmus R.; Mastalerz, Michael (Universität, 2022)
Anthropogenic greenhouse gases contribute to global warming. Among those gases, perfluorocarbons (PFCs) are thousands to tens of thousands times mo...
Gesehen am 08.12.2022
Keywords: Forschungsdaten; Datenbank